Antidiabetic Activity Test of Ethanolic Seri Leave’s (Muntingia Calabura L.) Extract in Male Rats Induced by Alloxan - Herlina Herlina; Annisa Amriani; Indah Solihah; Rizky Sintya (Science and Technology Indonesia, 2018)
Antidiabetic activity test of ethanol extract of seri leave (Muntingia calabura L.) rats induced by alloxan has been done. Male wistar albino rats are used as animal models which divided into 6 groups, normal group (aquadest), negative control group (Na CMC 0,5%), positive control group (glibenclamide 0,43 mg/200 gBB), and 1, 2, and 3 treatment groups (ethanol extract of seri leave 65, 130, dan 260 mg/kgBB). Rats blood glucose level after induced intraperitoneally by alloxan 130 mg/kgBB can be stated as diabetes when >200 mg/dL. Preprandial blood glucose levels are measured using DTN-410-K photometer, on day 0, 5, 10, and 15. The average result of AUC0-15 and percentage of decreasing blood glucose level for positive control group are 2732,5 and 37,43%, and 3 treatment groups (65 mg/kgBB, 130 mg/kgBB, and 260 mg/kgBB) 3105 and 28,90%; 2962,5 and 32,16%; 2810 and 35,66%. This point indicated that the ethanol extract of seri leave has an antidiabetic activity and there is no significant difference compared with glibenclamide (p<0,05). Percentage of blood glucose decrease level the third treatment group there is no significant difference compare with positive control group. According to the relation between percentage of blood glucose decrease level with dose, value of ED50 of ethanol extract of seri leave is 692,424 mg/kgBB.